(untitled) (Universal International Scientific Journal, 2026)
This article discusses the theoretical foundations and practical application areas of laser techniques in the study of materials. The role of laser techniques in materials science, chemistry, biology, ecology, and nanotechnology is also highlighted. It is emphasized that laser-based methods are distinguished by high sensitivity, rapid analysis, and the ability to perform non-contact measurements.